DAMPAK KEMISKINAN TERHADAP POLA MOBILITAS TENAGA KERJA ANTARSEKTOR DI INDONESIA - Evie Dian Pratiwi; Khusnul Ashar; Wildan Syafitri (Research Centre for Population, Indonesian Institute of Sciences, 2020)
Mobility can act as a stepping stone to get out of poverty. This research examines whether the effect of poverty encouraging or inhibiting the mobility of workers across sectors. By using data from the 2018 Indonesia National Labor Force Survey (Sakernas) that cover 8,869 respondents, this study applies multinomial regression models to analyse inter-sector mobility types among labors in Indonesia. The results show that low-income workers in the industrial and service sectors tend to have a 4.8% and 6.3% greater probability of transferring to the agricultural sector. However, agricultural workers that suffer from poverty choose to survive in the same sector due to the high cost of inter-sector mobility. Other findings show that older age and higher education level decreased the propensity to move across sectors. In the efforts to alleviate poverty, the role of the government is expected to be seen in two ways. Firstly, by facilitating workers to move into productive sectors, i.e. industrial and service sectors, and secondly, by increasing the productivity of the agricultural sector.